Capacity of Histoplasma capsulatum to Survive the Composting Process - Luisa Fernanda Gómez Londoño; Laura Carolina Pérez León; Juan Guillermo McEwen Ochoa; Alejandra Zuluaga Rodriguez; Carlos Alberto Peláez Jaramillo; Jose Miguel Acevedo Ruiz; María Lucia Taylor; Myrtha Arango Arteaga; María del Pilar Jiménez Alzate (Applied and Environmental Soil Science)
Histoplasma capsulatum (H. capsulatum) is a thermal-dimorphic fungus, the causal agent of histoplasmosis. Its presence in the environment is related with chicken manure due to their high nitrogen and phosphorus content. In Colombia, chicken manure is the most used raw material in the composting process; however, there is no information about the capacity of H. capsulatum to survive and remain viable in a composted organic fertilizer. To address this question, this study shows three assays based on microbiological culture and the Hc100 nested PCR. First, a composting reactor system was designed to transform organic material under laboratory conditions, and the raw material was inoculated with the fungus. From these reactors, the fungus was not isolated, but its DNA was detected. In the second assay, samples from factories where the DNA of the fungus was previously detected by PCR were analyzed. In the raw material samples, 3 colonies of H. capsulatum were isolated and its DNA was detected. However, after the composting process, neither the fungus was recovered by culture nor DNA was detected. In the third assay, sterilized and nonsterilized organic composted samples were inoculated with H. capsulatum and then evaluated monthly during a year. In both types of samples, the fungus DNA was detected by Hc100 nested PCR during the whole year, but the fungus only grew from sterile samples during the first two months evaluated. In general, the results of the assays showed that H. capsulatum is not able to survive a well-done composting process.